Feasibility of stereotactic radiotherapy for lung lesions and conventional radiotherapy for nodal areas in primary lung malignancies - Yeon Joo Kim; Su Ssan Kim; Si Yeol Song; Eun Kyung Choi (Radiation Oncology, 2018)
Abstract Background Combined stereotactic body radiotherapy (SBRT) for lung lesions and conventional radiotherapy (CRT) for nodal areas may be more effective than CRT alone in patients with locally advanced lung cancer. Methods This study included 21 patients with small primary lung tumors distant from the regional nodal areas. The SBRT dose was 40–60 Gy in 4 fractions. CRT doses were 66 Gy in 30 fractions for non-small cell lung cancer and 52.5 Gy in 25 fractions for small cell lung cancer. Results The median follow-up duration was 12 months, and the median survival was 13 months. The 1 year overall survival, local recurrence-free survival, and distant metastasis-free survival rates were 60.5, 84.8, and 62.1%, respectively. Two patients experienced in-field local recurrence combined with out-field regional recurrence and/or distant failure. The major recurrence pattern was distant failure (crude incidence, 43%). Three patients aged ≥79 years experienced grade ≥ 3 acute radiation pneumonitis, and one also had idiopathic interstitial pneumonia. Conclusion The combination of SBRT for the lung lesion and CRT for the nodal region seems to be effective and safe for lung malignancies. However, patients older in age and/or with underlying pulmonary disease require stricter lung dose constraints.